The effect of miniscalpel acupuncture and splint treatment for joint deformity of hand osteoarthritis: a case report - Kyongha Cho; Yoonsik Kim; Sang-Hoon Yoon (Integrative Medicine Research)
We are reporting the combined therapeutic effect of miniscalpel acupuncture and splint therapy on osteoarthritis of the hand accompanying severe joint deformity. The patient, female, 55 years of age, was diagnosed with symptomatic osteoarthritis of hand based on radiological examination and the American College of Rheumatology classification criteria. The patient was classified a grade 4 of Kellgren–Lawrence (KL) scale upon initial consultation. Over five months, the patient was treated with miniscalpel acupuncture with splint therapy. The patient's pain, decreased from 6–2 on numeral rating score (NRS) scale. The combined therapeutic effect of miniscalpel acupuncture and splint therapy seems to have positive results on OA of hand accompanying joint deformity, albeit being limited to a single case. Keywords: Acupotomy, Hand, Osteoarthritis, Case report